The portuguese Vitis vinifera L. germplasm: genetic relations between wild and cultivated vines - Cunha,Jorge (2010)
Portuguese wild vine populations are in an apparent geographic fringe of the species distribution. Despite, Portugal offers a unique richness in autochthonous cultivated varieties that contributes to the overall diversity of worldwide grapevine. In the different Portuguese agro-ecosystems, grapevine plays an important role either as a border culture or an extensive crop. During the last years wild vine populations have been identified but only in southern riverside ecosystems. To conclude if the local wild vine germplasm is involved in the origin of cultivated grapevine we used the OIV recommend six nuclear and four chloroplastidial microsatellite loci to genotype and to established phylogenetic relationships between wild plants and cultivated grapevines. Both native sylvestris and vinifera subspecies have a high genetic diversity and a sizeable number of rare alleles. Portuguese wild vine populations showed a high level of intra-population diversity with most of the genetic diversity conserved within each population. Wild vines seem to form a continuum and there is no clear population division. Despite, a low, but still significant, genetic differentiation can be detected among the analyzed populations. There seem to be a close genetic relation between the wild plants and cultivated varieties. Both subspecies mostly share the A and B chlorotypes, tipical of the Iberian germplasms. In some cases we found a close genetic relation between cultivated varieties and wild plants. Finally, some native grapevine cultivars have a higher genetic diversity that reveals introgression of foreign gene pool. This study contributes to establish the range of existing genetic variability in the Portuguese native grapevine and wild vines germplasm. It also provides a baseline for future monitoring of the genetic diversity of the species in Portugal and contributes with data to construct a core collection to preserve the existing variability and delineate conservation strategies for the wild vines.